The Effect of Brand Communication, Brand Experience, and Brand Image on Yamaha Brand Loyalty in West Jakarta: Brand Trust as a Mediation Variable - Ceri Hartono; Rodhiah Rodhiah (Budapest International Research and Critics Institute (BIRCI-Journal): Humanities and Social Sciences, 2021)
The purpose of this study was to empirically examine the effect of brand communication, brand experience, and brand image, brand trust on Yamaha Motor brand loyalty. The sampling technique used was the convenience sampling method, as many as 100 respondents who had used or owned a Yamaha Motorcycle in West Jakarta. Data collection by distributing online questionnaires using Google Forms. The analysis technique in this research is SEM using the SmartPLS 3.0 program. The results showed that brand communication and brand experience had a positive and significant effect on brand image, brand communication had a positive and insignificant effect on brand image, brand experience and brand image had a positive and significant influence on brand trust and brand loyalty, brand trust had a positive and significant effect positive and significant to brand loyalty.